Levels of functional disability in elderly people in Tanzania with dementia, stroke and Parkinson's disease. Issue 4 (17th March 2015) - Kisoli, Aloyce; Gray, William K.; Dotchin, Catherine L.; Orega, Golda; Dewhurst, Felicity; Paddick, Stella-Maria; Longdon, Anna; Chaote, Paul; Dewhurst, Matthew; Walker, Richard W.
Abstract : Background: Disability is associated with increasing age and poverty, yet there are few reliable data regarding disability amongst the elderly in low-income countries. The aim of this study was to compare disability levels for three of the most common neurological, non-communicable diseases: dementia, stroke and Parkinson's disease (PD). Methods: We performed a community-based study of people aged 70 years and over in 12 randomly selected villages in the rural Hai district of Tanzania. Participants underwent disability assessment using the Barthel Index, and clinical assessment for dementia, stroke and PD. Results: In a representative cohort of 2232 people aged 70 years and over, there were 54 cases of stroke, 12 cases of PD and estimated (by extrapolation from a sub-sample of 1198 people) to be 112 cases of dementia. People with stroke were the most disabled, with 62.9% having moderate or severe disability. Levels of moderate or severe disability were 41.2% in people with dementia and 50.0% in people with PD. However, the higher prevalence of dementia meant that, at a population level, it was associated with similar levels of disability as stroke, with 18.5% of 249 people identified as having moderate or severe disability having dementia, compared to 13.7% for stroke and 2.4% for PD. Conclusions: Levels of disability from these conditions is high and is likely to increase with demographic ageing. Innovative, community-based strategies to reduce disability levels should be investigated.